Development of an Edible Tray Composed of Potato Peel Starch and Coffee Pulp Fiber - José Arroyo-Villanueva; Gloria Muñoz-Villalobos; Raúl Siche; Roberto Carlos Chuquilín-Goicochea; Luz Quispe-Sanchez; Haley Figueroa-Avalos; Carmen Marín-Tello (Caraka Tani: Journal of Sustainable Agriculture, 2026)
Reducing plastic pollution and combating childhood anemia–which affects over 38.6% of Peruvian children–require sustainable, nutrient-rich alternatives. This study developed iron-fortified edible trays using potato peel starch (PPS), potato peel flour (PPF), and coffee pulp fiber (CPF), an agro-industrial waste containing 44 to 57 mg kg-1 of iron. Using an experimental design with 9 treatments and a control, 2 series were conducted using coarse (CPF-CT) and thin (CPF-TT) fiber. Physical (color, water absorption, and density) and mechanical (tensile and compressive strength) properties were evaluated via analysis of variance (ANOVA), Dunnett’s test, multiple linear regression, Pareto diagram, and principal component analysis (PCA). PCA revealed a critical trade-off between mechanical strength and impermeability, identifying an “optimal packing” zone at 10% CPF-TT, where fiber efficiently fills matrix voids. Consequently, formulations with 2.5% CPF-CT and 7.5% CPF-TT were selected as the most balanced candidates. These samples underwent subsequent Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and nutritional analysis. The formulation containing 50 g PPS, 15 g PPF, and 7.5 g CPF-TT exhibited the highest iron bioaccessibility. These results demonstrate the potential of coffee pulp-reinforced trays as a promising functional packaging solution to address both environmental waste and public health challenges.